2015
DOI: 10.1002/etc.2787
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity of binary and ternary mixtures of Cd, Cu, and Zn to Daphnia magna

Abstract: Standard static-exposure acute lethality tests were conducted with Daphnia magna neonates exposed to binary or ternary mixtures of Cd, Cu, and Zn in moderately hard reconstituted water that contained 3 mg dissolved organic carbon/L added as Suwannee River fulvic acid. These experiments were conducted to test for additive toxicity (i.e., the response to the mixture can be predicted by combining the responses obtained in single-metal toxicity tests) or nonadditive toxicity (i.e., the response is less than or gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

22
115
3

Year Published

2015
2015
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(141 citation statements)
references
References 35 publications
22
115
3
Order By: Relevance
“…In the right panel in Fig. 8 with [C A ] fixed at EC40, the introduction of C B leaded to the reduction of death rate and this is a similar pattern to the result of Cd-Zn mixture in Meyer et al (2015). The result also suggests that the same or similar reaction system of our Model III is involved in the combined effect of Cd-Zn mixture, although more detailed studies are definitely necessary.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…In the right panel in Fig. 8 with [C A ] fixed at EC40, the introduction of C B leaded to the reduction of death rate and this is a similar pattern to the result of Cd-Zn mixture in Meyer et al (2015). The result also suggests that the same or similar reaction system of our Model III is involved in the combined effect of Cd-Zn mixture, although more detailed studies are definitely necessary.…”
Section: Discussionsupporting
confidence: 68%
“…Although the C A is a reasonable model for the combined effects, it is important to investigate the limit of the model. Meyer et al (2015) showed that an introduction of low concentration leaded to the sharp reduction of death rate in Cd-Zn mixture. In the right panel in Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Because organisms of different developmental stages may differ in their sensitivity to a chemical, many regulatory agencies (USEPA 2002; OECD 2004) specify that acute toxicity tests should be started with D. magna younger than 1 day old. However, we have observed relatively high variability in the toxicity of Cd and Zn to D. magna neonates (Meyer et al 2015; Traudt et al 2015) and have demonstrated that this variablity is at least partly caused by major changes in sensitivity to the metals even within their first day postbirth (Traudt et al 2016). This methodologically induced variability can have important consequences, especially for predictions of metal-mixture toxicity when using results from individual-metal tests.…”
mentioning
confidence: 91%
“…We previously exposed D. magna to binary and ternary mixtures of Cd, Cu, Ni, and Zn in 48-h, static, nonrenewal lethality tests following USEPA-recommended procedures (Meyer et al 2015; Traudt et al 2015). We observed high variability in mortality in the binary and ternary mixtures that contained either Cd or Zn but relatively lower variability in mixtures containing Cu or Ni.…”
mentioning
confidence: 99%